How do nurses and physicians assess inter‐professional collaboration in long‐term care homes? A survey study - Christina Reese; Matthias Sehlbrede; Boris A. Brühmann; Erik Farin‐Glattacker (Wiley, 2021)
Abstract Aims To assess inter‐professional collaboration between nurses and physicians in long‐term care facilities and to determine if there are differences between subgroups of nurses. Design A cross‐sectional questionnaire survey was carried out between January 2018 and January 2020. Methods 408 health professionals (345 nurses, 63 physicians) from 37 nursing homes in Baden‐Wuerttemberg (Germany) participated in the survey. For data collection, the "Team‐Scale" and "Work Situation Questionnaire for nurses/physicians" instruments were used. Furthermore, five self‐generated items were employed assessing how ward rounds and documentation are implemented. For the evaluation, descriptive analyses, one‐way variance analyses (ANOVAs) and a multilevel analysis were performed. Results Inter‐professional teamwork was rated positively overall. However, the nursing staff usually gave more critical assessments than the physicians (for example, regarding mutual appreciation). Critical assessments could be used to initiate constructive change processes.